Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1968
DOI: 10.1002/pssb.19680300229
|View full text |Cite
|
Sign up to set email alerts
|

The Ordering of Ni3V

Abstract: Stoichiometric Ni3V undergoes a cubic + tetragonal ordering transition (A1 + D O , ) by means of nucleation and growth. Electron diffraction microscopy and other experimental techniques reveal that the reaction is continuous, proceedind in three stages: I. Nucleation of coherent particles of the ordered phase in clusters of common orientation; 11. Growth of these clustered nuclei to impingement forming isolated cells of unique orientationeach cell is subdivided into anti-phase domains; 111. Growth of the celle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
1
1

Year Published

1975
1975
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(47 citation statements)
references
References 19 publications
(8 reference statements)
6
39
1
1
Order By: Relevance
“…8c) shows the {100} and {110} superlattice reflections which do not exist after quenching. The diffraction pattern is similar to (12 spots are significantly weaker than {100} and {110} superlattice spots, which suggests that they originate from a different type of superlattice.…”
Section: Resultsmentioning
confidence: 78%
“…8c) shows the {100} and {110} superlattice reflections which do not exist after quenching. The diffraction pattern is similar to (12 spots are significantly weaker than {100} and {110} superlattice spots, which suggests that they originate from a different type of superlattice.…”
Section: Resultsmentioning
confidence: 78%
“…This is consistent with previous results of transmission electron microscopy studies that showed a ''tweed'' microstructure of quenched Ni 3 V. The tweed microstructure has a fine-scale distribution of internal strains, but no regions that are distinctly tetragonal. 17,21,22 Since the quenched sample had a high degree of the chemical order of the D0 22 structure, but none of the long-range tetragonality, we call it partially disordered.…”
Section: A Structurementioning
confidence: 99%
“…The domains are mutually arranged in a microtwin-type microstructure to minimize the elastic energy. 17,18,21,22 Such a microstructure can be optimized to minimize elastic energy at only one temperature, however. With changes in temperature, the ordered domains expand or contract anisotropically, generating internal elastic energy owing to geometrical mismatch between the lenticular packets.…”
Section: B Microstructure and Elastic Energymentioning
confidence: 99%
See 2 more Smart Citations